'Civil Wars: a view from the world of ancient Greece'. (3rd July 2019) - Cartledge, Paul
ABSTRACT: Our term 'civil war' has a direct correlate in the terminology of ancient Rome but the ancient Greeks, who practised civil war with a literal vengeance and great frequency, described it very differently: as a 'standing apart' and 'against' of one (citizen) faction against another.